Myasthenia gravis in Ceará, Brazil: clinical and epidemiological aspects - Aline de Almeida Xavier Aguiar; André Ferrer Carvalho; Carlos Mauricio de Castro Costa; José Marcelino Aragão Fernandes; José Artur Costa D'Almeida; Luís Edmundo Teixeira de Arruda Furtado; Francisco Marcos Bezerra da Cunha (Arquivos de Neuro-Psiquiatria)
A retrospective chart review was performed on patients diagnosed as having myasthenia gravis in Ceará State, Brazil and who were followed from October 1981 to June 2009. Clinical and epidemiologic aspects were evaluated. In this work, 122 patients were studied, of whom 85 (69.7%) were females and 37 (30.3%) were males. The disease duration ranged from five months to 50 years (8.9±8.1 years). Age at the first symptoms varied from 0 to 74 years (31.9±14.4 years). The first main symptoms and signs were ptosis, diplopia and limb weakness. Generalized myasthenia was the most common clinical presentation, but 5.1% (n=6) persisted as ocular myasthenia. Thymectomy was performed in 42.6% (n=52) of myasthenic patients. A thymoma was present in 10 patients. Serum acetylcholine receptor (AChR) antibodies were present in 80% (n=20) of specimens tested. The data presented are similar to those of studies performed in other countries.